2021
DOI: 10.1242/bio.058812
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila orthologue of the primary ciliary dyskinesia-associated gene, DNAAF3, is required for axonemal dynein assembly

Abstract: Ciliary motility is powered by a suite of highly conserved axoneme-specific dynein motor complexes. In humans the impairment of these motors through mutation results in the disease, Primary Ciliary Dyskinesia (PCD). Studies in Drosophila have helped to validate several PCD genes whose products are required for cytoplasmic pre-assembly of axonemal dynein motors. Here we report the characterisation of the Drosophila orthologue of the less known assembly factor, DNAAF3. This gene, CG17669 (Dnaaf3), is expressed e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 46 publications
(89 reference statements)
0
18
0
Order By: Relevance
“…However, of the other associated proteins identified, none appeared to have TPR domains or other features that would help clarify Dnaaf4 function. Filtering the data for proteins associated with motile cilia (zur Lage et al, 2021), we found two proteins of interest to be associated but at a P value that is below the threshold for significance (Fig. 4B).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, of the other associated proteins identified, none appeared to have TPR domains or other features that would help clarify Dnaaf4 function. Filtering the data for proteins associated with motile cilia (zur Lage et al, 2021), we found two proteins of interest to be associated but at a P value that is below the threshold for significance (Fig. 4B).…”
Section: Resultsmentioning
confidence: 99%
“…Pontin of R2TP is significantly associated (arrow). (B) The same dataset filtered to extract proteins associated with motile cilia (zur Lage et al, 2021). Pontin is the only associated protein to reach statistical significance.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations